REFORMULATING THE LEGAL STANDING OF INTERESTED THIRD PARTIES IN SUBMITTING PRETRIAL MOTIONS AGAINST THE TERMINATION OF INVESTIGATION OR PROSECUTION - Enos Syahputra Sipahutar; Faizin Sulistio; Abdul Madjid (CV. RADJA PUBLIKA, 2025)
This article discusses the urgency and necessity of reformulating the scope of third parties with legal standing to file a pretrial motion against the termination of investigation or prosecution. The study is motivated by a pretrial case in which the petition was rejected on formal grounds regarding the petitioner's legal standing, despite substantive indications of injustice in the law enforcement process. This research adopts a normative juridical method using statutory, conceptual, and case study approaches. The findings indicate that the limited interpretation of “interested third parties” as provided by the Constitutional Court in Decision Number 98/PUU-X/2012 does not fully reflect the principle of justice. Therefore, a redefinition of the scope of third parties particularly including suspects/defendants/convicts in separate case files is necessary to ensure equal access to justice and prevent discrimination in legal proceedings.